A strategic assessment of the future of U.S. Navy ship maintenance challenges and opportunities - Martin, Bradley; McMahon, Michael E.; Riposo, Jessie; Kallimani, James G.; Bohman, Angelena; Ramos, Alyssa; Schendt, Abby (RAND Corporation, 2017)
The U.S. Navy's ship inventory and the shipbuilding and repair industrial base that supports these ships have experienced significant changes. In the next 30 years, additional significant changes to the fleet composition and the maintenance requirements of the fleet are likely. This report assesses possible supply and demand capabilities in the ship maintenance workload for the Navy and notes long-term challenges facing mitigation efforts
"Prepared for the United States Navy."--Title page
Keywords: USA -- Navy; Schiff; Instandhaltung; Schiffbau; Bestand; United States / Navy / Operational readiness; United States / Navy; Warships / United States / Maintenance and repair; Defense industries / United States; Armed Forces / Operational readiness; Defense industries; Warships / Maintenance and repair; United States